2019
DOI: 10.1002/eahr.500014
|View full text |Cite
|
Sign up to set email alerts
|

Burden or Opportunity? Parent Experiences When Approached for Research in a Pediatric Intensive Care Unit

Abstract: Despite an ongoing need for pediatric research, low study enrollment may impede study completion, particularly in critical care. We conducted a prospective cross-sectional survey and chart review study to assess parent experiences with research in a pediatric intensive care unit (PICU). Of the 80 parents who completed the study survey, 54% were approached to participate in a research study in the PICU, and 93% agreed to participate. Motivators included altruism, low burden, low risk, and research that would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Furthermore, few existing studies on pediatric biorepositories enroll patients from a general pediatric population and rather focus on pediatric patients impacted by rare diseases such as congenital heart disease and cancer [ 13 , 16 , 18 , 19 ]; enrollment rates in such biorepositories range from 55-97% [ 14 , 18 – 21 ]. To our knowledge, this is the first study of demographic and epidemiologic predictors of enrollment in a pediatric biorepository examining characteristics of pediatric patients themselves (rather than their parents/guardians) or conducted in a pandemic setting [ 14 , 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, few existing studies on pediatric biorepositories enroll patients from a general pediatric population and rather focus on pediatric patients impacted by rare diseases such as congenital heart disease and cancer [ 13 , 16 , 18 , 19 ]; enrollment rates in such biorepositories range from 55-97% [ 14 , 18 – 21 ]. To our knowledge, this is the first study of demographic and epidemiologic predictors of enrollment in a pediatric biorepository examining characteristics of pediatric patients themselves (rather than their parents/guardians) or conducted in a pandemic setting [ 14 , 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parents are generally willing to enroll children in clinical trials [ 24 26 ]. Parents agree to their children's participation of there is a higher perceived benefit to their children [ 15 , 23 ]. Parents tend to overestimate the benefits of research on the well-being of their children and underestimate any risks in donating samples [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A practical example emerged from a study carried out at a US pediatric intensive care unit, where it is routine practice for administration to approach parents on admission, with a consent form for enrolling the child in the pediatric biobank. However, out of 80 parents that later agreed to take part in a study, only 54% confirmed that they had already been approached in relation to research ( 104 ).…”
Section: Specific Societal Issuesmentioning
confidence: 99%
“…In one study examining enrollment of seriously ill children in research in the pediatric intensive care unit, only 74% of parents reported they felt respected during a research approach and 63% believed that they had adequate time to decide about participation, suggesting both of these as targets for research teams to consider when attempting to enroll patients into research studies. 9 In addition, for stakeholder driven studies such as this, study teams may bring to bear principles of community engaged research to research conducted within the institution. Respecting that distinct ethical issues may arise with engaging children and parents in community-based research approaches, strategies that embody stakeholder involvement at all stages of the research process will ideally incorporate the viewpoints of diverse groups.…”
mentioning
confidence: 99%